2019
DOI: 10.1016/j.matt.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Unlock Shelf-Stable Ti3C2T (MXene) Nanosheet Dispersions

Abstract: MXenes are prone to oxidize and degrade quickly in a matter of days. Here, the use of antioxidants, such as sodium L-ascorbate, is demonstrated as an effective approach to arrest the oxidation of colloidal and dehydrated Ti 3 C 2 T x MXene nanosheets. The success of the method is evident as the Ti 3 C 2 T x nanosheets maintain their composition, morphology, electrical conductivity, and colloidal stability. This method addresses the most pressing challenge in the field of MXene engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
405
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(415 citation statements)
references
References 38 publications
10
405
0
Order By: Relevance
“…The response remained at around −9.2% over a month period, indicating a good long-term stability of the Ti 3 C 2 T x /WSe 2 sensor. This suggests that our hybridization process might also be an effective strategy to overcome the oxidation of MXenes 37,45 . Fig.…”
Section: Chemical Composition Of Ti 3 C 2 T X /Wse 2 Nanohybrids Figmentioning
confidence: 94%
“…The response remained at around −9.2% over a month period, indicating a good long-term stability of the Ti 3 C 2 T x /WSe 2 sensor. This suggests that our hybridization process might also be an effective strategy to overcome the oxidation of MXenes 37,45 . Fig.…”
Section: Chemical Composition Of Ti 3 C 2 T X /Wse 2 Nanohybrids Figmentioning
confidence: 94%
“…This might also be attributed to the existence of intercalants (DMSO) between Ti 3 C 2 T x nanosheets and lack of a resulted densified structure as what was featured in pristine films. It is worth mentioning that addition of polyanionic salts or reductants also protects Ti 3 C 2 T x nanosheets from oxidation, but these protocols could not make a Ti 3 C 2 T x film with both high strength and conductivity. Besides, proton acid processing method can be applied to any concentration of Ti 3 C 2 T x dispersion for the fabrication of pristine Ti 3 C 2 T x assemblies.…”
Section: Materials Performance and Applications Of Original/pristine mentioning
confidence: 99%
“…These results are noteworthy for two reasons:F irst is their practical importance.Second, they provide,for the first time,direct evidence for anion adsorption at the edges of aTi 3 C 2 T z flake.This work complements our prior work, where we concluded that the edges of Ti 3 C 2 T z sheets were positively charged. [23] Quite recently,Zhao et al [36] showed that oxidation can be mitigated by adding sodium ascorbate and related salts,t o Ti 3 C 2 T z colloids.F urther,b yu sing molecular dynamic simulations they demonstrated that the ascorbate anions absorb at the edges,t hough this was not confirmed experimentally.I n their work, the authors held their colloidal suspensions for 3weeks in closed containers as opposed to am onth in open containers herein.…”
Section: Angewandte Chemiementioning
confidence: 99%